Arthonia buelliae sp. nov. (Arthoniaceae, Arthoniales, Ascomycota) and other noteworthy lichenicolous fungi from the Primorye Territory of Russia - Zhurbenko, Mikhail P. (Phytotaxa, 2021)
Arthonia buelliae, a gall-inducing lichenicolous ascomycete from Russia growing on Buellia stellulata, is described as new to science. The species is characterized by immersed ascomata, I+ blue then reddish-brown and K/I+ blue hymenia, 8-spored, I−, K/I− asci and (1–)2–3-trans-septate or rarely submuriform, brown, granulate ascospores. Polycoccum stellulatae is newly documented for Asia and Russia, and Sclerococcum sphaerale for Russia. To date, 41 species of lichenicolous fungi are known from the Primorye Territory of Russia, which amounts to no more than 20% of their true diversity in this region according to estimates of the spatial Lichenicolous Index.